How Guest Delight Affected Hotel Pricing before and during Covid-19 Pandemic - Domagoj Nikolić; Andrea Mitrović (International School for Social and Business Studies, 2021)
Purpose: This study aimed to establish the extent to which Dubrovnik upscale hotels delight their guests and if such "wow effects" affect their rates. Study design/methodology/approach: TripAdvisor pages of 15 Dubrovnik upscale hotels were searched for guest delight attributes and hotel rates, and analysed with descriptive statistics, linlog regression and Spearman correlation. Findings: Dubrovnik upscale hotels provide solid services, but still lack the "wow effect". In this context, guest delight has no discernible effect on hotel rates. Hotels should focus more on personalization and guest delight in their search for extractable value particularly during the Covid-19 pandemic characterized by the diminished occupancy and rates. Originality: Although guest delight was studied relatively extensively, this is the first time it was done in relation to hotel rates. https://www.doi.org/10.53615/2232-5697.10.85-96